Acid‐Induced Dissolution of Andesite: Evolution of Permeability and Strength. Issue 1 (17th January 2019) - Farquharson, Jamie I.; Wild, Bastien; Kushnir, Alexandra R. L.; Heap, Michael J.; Baud, Patrick; Kennedy, Ben
Abstract: Volcanic systems often host crater lakes, flank aquifers, or fumarole fields that are strongly acidic. In order to explore the evolution of the physical and mechanical properties of an andesite under these reactive chemical conditions, we performed batch reaction experiments over timescales from 1 day to 4 months. The experiments involved immersion of a suite of samples in a solution of 0.125 M sulfuric acid (pH ∼0.6). Periodically, samples were removed and their physical and mechanical properties measured. We observe a progressive decrease in mass, coincident with a general increase in porosity, which we attribute to plagioclase dissolution accompanied by the generation of a microporous diktytaxitic groundmass due to glass dissolution. Plagioclase phenocrysts are seen to undergo progressive pseudomorphic replacement by an amorphous phase enriched in silica and depleted in other cations (Na, Ca, and Al). In the first phase of dissolution ( t = 24–240 hr), this process appears to be confined to preexisting fractures within the plagioclase phenocrysts. However, ultimately these phenocrysts tend toward entire replacement by amorphous silica. We propose that the dissolution process results in the widening of pore throats and the improvement of pore connectivity, with the effect of increasing permeability by over an order of magnitude relative to the initial measurements. Compressive strength of our samples was also modified, insofar as porosity tends to increase (associated with a weakening effect). We outline broader implications of the observed permeability increase and strength reduction for volcanic systems including induced flank failure and related hazards, improved efficiency of volatile migration, and attendant eruption implications. Plain Language Summary: Where water is present in volcanic environments, it is often strongly acidic due to the presence of dissolved gases such as sulfur dioxide (involving similar process to that which forms acid rain). Indeed, it is estimated that almost 800 acidic volcanic lakes exist worldwide. In terms of volcanic hazard it is important to understand the influence of such acids on volcanic rocks. We performed experiments where samples of volcanic rock were submerged in an acid solution for varying lengths of time (we used a strong concentration of sulfuric acid in order to mimic the chemistry of a natural acid lake). We find that some of the minerals in our samples dissolve over time when in contact with the acid. Ultimately, this makes the rock weaker and more porous and increases the ability for fluid to flow through the rock. These results indicate that certain large‐scale mechanisms might occur more frequently in nature when there are acidic conditions, such as the collapse of part of the side of the volcano or the rim of its crater. In this paper we describe the processes occurring on the microscale and outline broad implications for our results in the context of volcanic areas. Key Points: Volcanic environments often host strongly acidic lakes or aquifers Prolonged exposure of andesite to sulfuric acid induces mineral dissolution As a consequence, permeability and porosity increase, while mass decreases